Pengaruh Pengalaman Kerja, Motivasi Dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan PT Sumitomo Wiring System Batam - Noviani, Ami; Suhardi, Suhardi (Manajemen & Bisnis Jurnal, 2025)
This study was conducted to determine how factors such as work experience, motivation, and career development affect employee job satisfaction at PT Sumitomo Wiring System Batam. The research methodology used in this study is quantitative and descriptive. A total of 138 operator personnel from PT Sumitomo Wiring System Batam in 2024 were included in this study as a population. The saturated sampling approach was used to ensure that the entire population was included. Data quality testing, classical assumptions, influence, and hypothesis testing are part of the data analysis process. According to multiple linear regression, work experience is responsible for 23.2% in explaining job satisfaction, while motivation explains 33.3% in job satisfaction, and career development is responsible for 59.6% in explaining job satisfaction. In the results of the determination coefficient (R2), the three tested together contributed 80.5% to the level of job satisfaction experienced by individuals. The findings of the t-test and F-test confirm that there is a positive and statistically significant relationship between job satisfaction influenced by factors including work experience, motivation, and career development.